MO198: Outcomes with Finerenone in Patients with Stage 4 Chronic Kidney Disease and Type 2 Diabetes: A Fidelity Subgroup Analysis. (3rd May 2022) - Sarafidis, Pantelis; Ruilope, Luis; Anker, Stefan D; Agarwal, Rajiv; Pitt, Bertram; Filippatos, Gerasimos; Rossing, Peter; Tuttle, Katherine; Boletis, Ioannis; Toto, Robert; Wanner, Christoph; Zhi-Hong, Liu; et al.
Abstract: BACKGROUND AND AIMS: Patients with stage 4 chronic kidney disease (CKD) and type 2 diabetes (T2D) have a high residual risk of cardiovascular (CV) and kidney disease progression, and effective treatment options to reduce the risk are limited. The non-steroidal selective mineralocorticoid receptor antagonist finerenone has previously demonstrated significant cardiorenal benefits versus placebo in patients with stage 1–4 CKD [1 –3 ]. This FIDELITY subgroup analysis investigated the effects of finerenone in patients with stage 4 CKD [estimated glomerular filtration rate (eGFR) <30 mL/min/1.73 m 2 ) versus those with stage 1–3 CKD (eGFR ≥ 30 mL/min/1.73 m 2 ). METHOD: FIDELIO-DKD and FIGARO-DKD were phase III trials of patients with CKD and T2D randomised 1:1 to finerenone or placebo. FIDELITY was an individual patient-level prespecified pooled efficacy and safety analysis of these studies. Efficacy outcomes included change in urine albumin-to-creatinine ratio (UACR) between baseline and month 4, change in eGFR over time, a kidney composite outcome (kidney failure, a sustained ≥57% decrease in eGFR from baseline over ≥ 4 weeks or renal death) and a CV composite outcome [CV death, non-fatal myocardial infarction, non-fatal stroke or hospitalization for heart failure (HHF)], as well as the individual components of these composite outcomes. RESULTS: Of 13 023 patients included in the analysis, 890 patients (6.8%) had stage 4 CKD; key baseline characteristics are listed in Table 1 . In patients with stage 4 CKD, finerenone reduced UACR by 31% vs placebo between baseline and month 4 [ratio of least-squares (LS) mean change 0.69; 95% confidence interval (CI) 0.63–0.77), an effect maintained for the duration of the study. Total eGFR slope (LS mean change in eGFR from randomisation to end of treatment) in patients with stage 4 CKD was –0.7 mL/min/1.73 m 2 /year with finerenone versus –1.6 mL/min/1.73 m 2 /year with placebo; the chronic eGFR slope (LS mean change in eGFR from month 4 to end of treatment) was –1.8 mL/min/1.73 m 2 /year with finerenone vs –3.2 mL/min/1.73 m 2 /year with placebo. The hazard ratio (HR) for risk of the kidney composite in stage 4 CKD was 1.01 (95% CI 0.75–1.37; Figure 1 ) for finerenone versus placebo. Reduction in risk of sustained ≥ 57% decrease in eGFR with finerenone (stage 4 CKD: HR 0.69, 95% CI 0.43–1.11) was similar between CKD subgroups ( p interaction  = 0.71). Reduction in risk of the composite CV outcome (stage 4 CKD: HR 0.78, 95% CI 0.57–1.07) and HHF (stage 4 CKD: HR 0.99, 95% CI 0.62–1.58) was also consistent between CKD subgroups ( p interaction  = 0.67 and 0.31, respectively). Overall, incidences of adverse events were balanced between treatment arms in patients with stage 4 CKD and stage 1–3 CKD. The incidence of hyperkalaemia leading to permanent discontinuation was low in patients with stage 4 CKD (3.2% versus 2.2% for finerenone versus placebo). CONCLUSION: The cardiorenal benefits and safety profile of finerenone in FIDELITY were also observed in the subgroup of patients with stage 4 CKD.